IMMUNOSUPPRESIVE EFFECTS OF THE METHANOLIC EXTRACT OF CHRYSOPHYLLUM CAINITO LEAVES ON MACROPHAGE FUNCTIONS - Arana-Argáez, VÃctor Ermilo; Chan-Zapata, Ivan; Canul-Canche, Jaqueline; Fernández- MartÃn, Karla; MartÃn-Quintal, Zhelmy; Torres-Romero, Julio Cesar; Coral-MartÃnez, Tania Isolina; Lara-Riegos, Julio Cesar; RamÃrez-Camacho, Mario Alberto (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The aim of this work was to evaluate the immunomodulatory effect of the methanol extract(MeOH) from Chrysophyllum cainito leaves on the MΦs functions.Material and Methods: Peritoneal murine MΦs isolated from Balb/c mice were treated with the MeOH extractand stimulated with LPS. The effect on the phagocytosis was evaluated by flow cytometry assay. The nitricoxide (NO) and hydrogen peroxide (H2O2) production was measured by the Griess reagent and phenol redreaction, respectively. Levels of IL-6 and TNF-was measured using an ELISA kit. Viability of MΦs and Verocells was determined by the MTT method.Results: The MeOH extract of C. cainito leaves inhibited significantly the phagocytosis, and decreased IL-6 andTNF-α production as well as NO and H2O2 released by the MΦs, in a concentration-dependent manner. Inaddition, MeOH extract of C. cainito showed low cytotoxicity effect against the cells.Conclusion: These results suggest that MeOH extract of C. cainito leaves has an immunosuppressive effect onmurine MΦs, without effects on cell viability. GC-MS chromatogram analysis of MeOH extract showed thatlupeol acetate and alpha-amyrin acetate are the principal compounds.